Sintering response and mechanical properties of microwave sintered 316L Powder Blends - Mascarenhas, João (2009)
Microwave sintering can be an efficient, economic and valuable approach for the processing of some PM materials. Recent findings on the ability of powdered metals to absorb and dissipate microwave radiation, opened new opportunities for the PM world. Being the particle size of the metallic powders one of the key parameters that rules the heating rate and the temperature performance during microwave sintering, work has been carried out on compacts of 316L powder blends with 60, 50, 25 and 7 m mean particle sizes, at 1150ºC for 30 minutes in a 2.45 GHz-1000 W microwave oven. Green and sintered densities and corresponding transverse rupture strength (TRS) are reported as well as hardness and porosity. Densities in excess of 95% were attained for the finer powders. TRS tests were performed on all but the 7 m powder specimens, being the highest value of 630 MPa obtained for the 25 m powder specimens